Perceived Ease of Use as a Predictor of Social Networking Technologies Adoption in Institutions of Higher Learning in Uganda - Keefa, Bwiino; Mayoka, Kituyi Geoffrey; Musenze, Ibrahim A. (Global Journal of Computers & Technology, 2016)
Social Networking Technologies (SNTs) play a major role in education by improving student academic performance through a participatory culture. The purpose of this study was to examine the influence of Perceived Ease of Use (PEOU) on the adoption of Social Networking Technologies in institutions of higher learning in Uganda. A cross sectional survey methodology was employed to gather data from 146 institutions of higher learning on the variables captured by the modified PEOU construct. Results of correlation and regression analysis indicated that a positive and significant relationship exists between Perceived Ease of Use and SNTs adoption. These findings have theoretical implications for models of SNTs adoption by aligning Perceived Ease of Use as a Significant Predictor of SNT adoption. The findings also have practical interventions designed at increasing use of SNTs by pointing out that lecturers and students should conceptualize the aspects of technology-enhanced tools and realize the potential of the use of SNTs in the lecturing and learning contexts respectively.
Keywords: Social Networking Technologies; Perceived Ease of Use; Perceived Usefulness; Technology Acceptance Model; User Generated Content; SNT Adoption